Understanding graffiti: multidisciplinary studies from prehistory to the present - Lovata, Troy; Olton, Elizabeth (Left Coast Press, 2015)
"This collection of original articles brings together for the first time the research on graffiti from a wide range of geographical and chronological contexts and shows how they are interpreted in various fields. Examples range as widely as medieval European cliff carvings to tags on New York subway cars to messages left in library bathrooms. In total, the authors legitimize the study of graffiti as a multidisciplinary pursuit that can produce useful knowledge of individuals, cultures, and nations. The chapters -represent 20 authors from six countries; -offer perspectives of disciplines as diverse as archaeology, history, art history, museum studies, and sociology; -elicit common themes of authority and its subversion, the identity work of subcultures and countercultures, and presentation of privilege and status"--